Correction: theoretical study on the mechanism, chemo- and enantioselectivity of the Ag- vs. Rh-catalyzed intramolecular carbene transfer reaction of diazoacetamides. Issue 32 (18th July 2022) - Song, Qingmin; Wu, Jiayi; Tzouras, Nikolaos V.; Wu, Yong; Nolan, Steven P.
Abstract : Correction for 'Theoretical study on the mechanism, chemo- and enantioselectivity of the Ag- vs. Rh-catalyzed intramolecular carbene transfer reaction of diazoacetamides' by Qingmin Song et al., RSC Adv., 2022, 12, 18197–18208, ; https://doi.org/10.1039/D2RA01298G .